The Role-Playing Method To Improve Learning Outcomes Of Arabic Speaking Skills: Process And Student Perception: Role-Playing Method To Improve Learning Outcomes Of Arabic Speaking Skills: Process And Student Perception - Zulpianto, Redi; ilhami, rosita; M Daud, Sulhi (Yayasan Daarul Qimmah Gorontalo, 2024)
This research aims to determine students' processes and perceptions of Arabic learning skills using the role-playing method. The population in this study was 18 grade 10th students at MAS Mamba'ul Ulum Jambi. This research is qualitative research with a descriptive method. The data was collected by observation, interview, and documentation. The researcher analyzed the data using triangulation techniques. The process is a teacher appoints 2 or 3 students to a group, divides the roles, and instructs other students to pay attention. The advantages are: a) students enjoy learning using the role-playing method, b) students easy to memorize vocabulary, and c) there is an increase in students' Arabic-speaking learning outcomes with a score of 62.77 increasing to 84.72 after learning using the role-playing method. However, the researcher also finds a drawback, namely that it takes a long time to implement and disturbs other classes because the class becomes noisier.